The sustainability of restorative justice - Kenny, Paula; Leonard, Liam (Advances in sustainability and environmental justice,, 2014)
Restorative justice is a concept which could have significant implications for both the law and social regulation. In this book, the authors give an insight to how the introduction of these techniques has been received in the Republic of Ireland, shedding light on what could be the key to developing new responses to crime.